“Dynamic Monitoring of Hypothyroidism During Pregnancy” article [Response to Letter] - Abadi KK (Dove Medical Press, 2023)
Kidus Kebede Abadi Daruxannan General Hospital, Somaliland, SomaliaCorrespondence: Kidus Kebede Abadi, Email kiduskebedetox@gmail.com